Commentary—Disenchantment with the “Egalitarian Revolution” - Kenneth S. Tollett (Washington University Law Quarterly, 1979)
When I heard the discussion this morning, what came to mind is the problem in law of the different levels on which one has to operate in trying to address or deal with this problem.
Keywords: Public schools; Desegregation